ChemInform Abstract: Diastereoselective and Enantioselective Silylation of 2‐Arylcyclohexanols. Issue 40 (October 2015) - Wang, Li; Akhani, Ravish K.; Wiskur, Sheryl L.
Abstract The kinetic resolution proceeds best in the presence of silyl chloride (II) and is selective for trans diastereomers.